Cytokines in Immune-mediated “Non-infectious” Uveitis - Kalogeropoulos, Dimitrios; Kanavaros, Panagiotis; Vartholomatos, Georgios; Moussa, George; Chʼng, Soon Wai; Kalogeropoulos, Chris (Klinische Monatsblätter für Augenheilkunde, 2023)
Uveitis is a significant cause of ocular morbidity and accounts for approximately 5 – 10% of visual impairments worldwide, particularly among the working-age population. Infections are the cause of ~ 50% cases of uveitis, but it has been suggested that infection might also be implicated in the pathogenesis of immune-mediated “non-infectious” uveitis. There is growing evidence that cytokines (i.e., interleukins, interferons, etc.) are key mediators of immune-mediated “non-infectious” uveitis. For example, activation of the interleukin-23/interleukin-17 signalling pathway is involved in immune-mediated “non-infectious” uveitis. Studies in animal models have been important in investigating the role of cytokines in uveitis. Recent studies of clinical samples from patients with uveitis have allowed the measurement of a considerable array of cytokines even from very small sample volumes (e.g., aqueous and vitreous humour). The identification of complex patterns of cytokines may contribute to a better understanding of their potential pathogenetic role in uveitis as well as to an improved diagnostic and therapeutic approach to treat these potentially blinding pathologies. This review provides further insights into the putative pathobiological role of cytokines in immune-mediated “non-infectious” uveitis.
Keywords: uveitis; cytokines; autoimmune; non-infectious; diagnosis; treatment